Sacrificing the Few to Save the Many: The Moral Economy of Resettlement to Norway - Weiss, Nerina (Refuge)

(untitled) (Centre for Refugee Studies, York University, 2026)
This article explores how Norwegian resettlement officers navigate moral dilemmas when selecting refugees who are deemed both deserving of protection and too vulnerable, costly, or risky to resettle. It analyzes resettlement officers’ moral distress, discretionary power, and coping strategies and develops a moral economy perspective on refugee resettlement in a universalist welfare state. The analysis reveals that these dilemmas reflect fundamental contradictions within the resettlement system, at the intersection of humanitarian commitment, national legal and social norms, and municipal capacity. These moral tensions create a space where human suffering is neither ignored nor easily resolved but continuously present.